Analisis Dampak Perilaku Konsumtif Remaja: Perspektif Riba Dalam Penggunaan PayLater di Platform E-Commerce Shopee - Nayla Izzatul Laili; Madian Muhammad Muchlis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Discounts and promotions are the main motivation, while most feel that the financial risks outweigh the benefits. This research aims to highlight aspects of financial risk associated with adolescent consumption choices in the e-commerce era so that this study contains an analysis of the impact of using the